2008
DOI: 10.1080/1065657x.2008.10702354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vegetable, Fruit And Garden (VFG) Waste Compost on Soil Physical Properties

Abstract: Compost and other organic amendments have been proven to improve the soil physical quality. In Flanders, vegetable, fruit and garden (VFG) wastes are collected selectively and composted. We studied the effects of the combined application of three different doses of VFG compost and cattle slurry and one treatment with only mineral N applied, during 9 years on a range of soil physical properties: aggregate stability, saturated hydraulic conductivity, bulk density, total pore volume and soil moisture retention. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…Hence, it is necessary to note the one exception (Hati et al 2007) in Table 3, which displayed a slightly higher PAW for the control; this may be linked to the high clay content. The data by Leroy et al (2008) with reduced PAW in compost-amended soils were not well predicted. Except for these studies, the data here confirmed their conclusion (Rawls et al 2003) that water retention at FC is more strongly affected by OC content than that at WP, which means increases in PAW.…”
Section: Impact Of Texture and Carbon Contentmentioning
confidence: 93%
See 4 more Smart Citations
“…Hence, it is necessary to note the one exception (Hati et al 2007) in Table 3, which displayed a slightly higher PAW for the control; this may be linked to the high clay content. The data by Leroy et al (2008) with reduced PAW in compost-amended soils were not well predicted. Except for these studies, the data here confirmed their conclusion (Rawls et al 2003) that water retention at FC is more strongly affected by OC content than that at WP, which means increases in PAW.…”
Section: Impact Of Texture and Carbon Contentmentioning
confidence: 93%
“…Two studies are not included in Fig. 7, Bandyopadhyay et al (2011) did not report FC or WP, and in the study of Leroy et al (2008), the reductions in FC and PAW cannot be explained. Concerning statement 1 of Khaleel et al (1981), there appears to be a trend confirming larger percent increases in FC and WP for coarser-textured soils (Fig.…”
Section: Impact Of Organic Waste Additionmentioning
confidence: 99%
See 3 more Smart Citations